English Education Students’ Perceptions of the Use of TikTok’s Speak Fast Challenge for Improving Speaking Skills (A Case Study on the 8th-Semester Students) - Maulia, Vina Citra Tri; Bahri, Seful (Jurnal Pendidikan Indonesia, 2025)
TikTok is a short video-based social media that has recently become very popular and widely used by people worldwide. TikTok can not only be used as an entertainment medium but can also be utilized as a learning medium, including improving speaking skills. This study explores English education students’ perception of the use of TikTok’s Speak Fast Challenge to improve speaking skills. Using a qualitative case study research design, data were collected through in-depth interviews and observations of six eighth-semester English education students at Universitas Negeri Semarang. The data obtained were analyzed qualitatively using thematic analysis. The results of this study show that the students gave a positive perception. They found it interesting, fun, not boring, flexible, and motivating. It helped them improve their speaking fluency, speed, pronunciation, and confidence. However, the students also faced challenges, including a lack of confidence, difficulty following the fast tempo, slow internet connection, low video quality, and an unconducive environment. Despite its shortcomings, the Speak Fast Challenge shows potential as a learning support tool to improve speaking.